1995
DOI: 10.1103/physrevb.52.6162
|View full text |Cite
|
Sign up to set email alerts
|

Radial distribution function of a new form of amorphous diamond shock induced fromC60fullerene

Abstract: The radial distribution function of a new form of amorphous diamond, synthesized from C60 fullerene by shock compression and rapid quenching, was obtained from an electron difFraction pattern using an imaging plate. The present amorphous diamond was essentially amorphous material based on difFractometry. Analysis of the local structure around an atom revealed that the amorphous material was distinguishable not only from sp -based amorphous material but also from some tetrahedrally coordinated amorphous carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…Indeed, in early experiments very hard and stiff materials were synthesised (stable under ambient conditions) by compressing fullerite under high pressure [6]. Subsequently, these phases have been characterised experimentally by determining their structural, mechanical, and optical properties [7,8,9,10,11,12,13,14,15] revealing a plethora of ordered (polymerised fullerenes) and disordered (amorphous) carbon phases (see [7] for a review).Based on electron diffraction experiments, shockcompressed fullerite [16], has been conjectured to be a new form of amorphous diamond exhibiting IRO [7]. Furthermore, it has been argued that the mechanical properties are determined by remnants of (partially) intact fullerene cages distinguishing these phases from tetrahedrally coordinated amorphous carbon (ta-C) produced by ion-beam techniques.…”
mentioning
confidence: 99%
“…Indeed, in early experiments very hard and stiff materials were synthesised (stable under ambient conditions) by compressing fullerite under high pressure [6]. Subsequently, these phases have been characterised experimentally by determining their structural, mechanical, and optical properties [7,8,9,10,11,12,13,14,15] revealing a plethora of ordered (polymerised fullerenes) and disordered (amorphous) carbon phases (see [7] for a review).Based on electron diffraction experiments, shockcompressed fullerite [16], has been conjectured to be a new form of amorphous diamond exhibiting IRO [7]. Furthermore, it has been argued that the mechanical properties are determined by remnants of (partially) intact fullerene cages distinguishing these phases from tetrahedrally coordinated amorphous carbon (ta-C) produced by ion-beam techniques.…”
mentioning
confidence: 99%
“…This is further illustrated by the rapid amorphization of the present phase and the fact that static hot compression experiments 9,39,40 yielded only amorphous material with mixed sp 2 − sp 3 bond hybridization at the pressure and temperature comparable to our experiment. Interestingly, conventional shock wave loading of C 60 yielded amorphous diamondlike material 25 at lower loading and unloading rates. The ultrafast nature of loading to elevated pressure and temperature in our experiment and the loss of the crystallinity of the present phase at ambient conditions over a short period ͑compared to diamond͒ indicate that the present structure indeed represents an intermediate structural stage in the graphite-diamond transition.…”
Section: Figmentioning
confidence: 99%
“…23,24 Conventional shock wave loading of C 60 fullerene yielded amorphous diamond. 25 The differences in heating and strain rates, porosity, starting materials, pressure-temperature conditions, and inherent kinetics for phase transitions may strongly affect the nature of the structures formed upon loading and upon recovery.In this work, we utilize laser-induced shock wave loading 26,27 at higher strain and heating rates and shorter loading durations to probe possible transient structures on the path of graphite-diamond transition. The starting materials were a mixture of graphite and copper powders ͑3:16 by mass͒.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of covalent bonds makes the new phases very stable. Hirai et al [12] reported amorphous diamond prepared from C 60 by shock compression. Based on the indirect scratching observations [13] and measurements made by time-resolved acoustic microscopy [ 14], Blank et aL [9] postulated that superhard and ultrahard phases could be synthesized from C 60 .…”
Section: Introductionmentioning
confidence: 99%